The Contribution of Information, Communication, and Technology (ICT) in Supply Chain Performance at Kebun Bangelan - Fadiah Retno Imara; Yani Nurhadryani; Bagus Sartono (Dinasti International Journal of Education Management and Social Science, 2025)
Indonesia is the fourth largest coffee producer after Brazil, Vietnam, and Colombia, with an average coffee production value in Indonesia in 2022 reaching around 789.97 thousand tons per year. In 2014-2023, the largest type of coffee production was robusta coffee at 72.71% or 517.41 thousand tons. Kebun Bangelan, which produces coffee beans. This study aims to analyze the contribution of ICT, quality information sharing, supply chain collaboration, and supply chain performance. A mixed-methods approach was used in this research to determine the contribution of ICT by distributing questionnaires and depth-interviews with Kebun Bangelan employees. The coffee bean supply chain begins with planting raw materials, and production using machine technology. ICT used by Kebun Bangelan includes computers and supply chain data processing through applications, namely System Application and Product in Data Processing (SAP), spreadsheet, and Microsoft Office. The contribution of ICT shows a strong correlation with information sharing quality, a good correlation with supply chain collaboration, and a good correlation with supply chain performance.